2020
DOI: 10.1182/blood.2020008367
|View full text |Cite
|
Sign up to set email alerts
|

Waning of SARS-CoV-2 RBD antibodies in longitudinal convalescent plasma samples within 4 months after symptom onset

Abstract: Perreault and colleagues examined antibody titers in sequential samples from serum donors recovering from COVID-19 and demonstrated that antibody titers fall over 3-4 months. These results have important implications for convalescent serum collection and seroprevalence studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
107
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 29 publications
(27 reference statements)
16
107
3
2
Order By: Relevance
“…While our results are only relevant for the first several weeks after infection, experimental evidence suggests that antibody titers are relatively stable for at least a period of 5 months after symptoms onset [ 2 , 3 , 55 ], with only ~3 fold decrease in antibodies levels in ~80–100 days [ 2 , 3 ]. This suggests that antibody production does not halt completely once SARS-CoV-2 viral loads go below the detection limit, which is typical following many viral infections.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While our results are only relevant for the first several weeks after infection, experimental evidence suggests that antibody titers are relatively stable for at least a period of 5 months after symptoms onset [ 2 , 3 , 55 ], with only ~3 fold decrease in antibodies levels in ~80–100 days [ 2 , 3 ]. This suggests that antibody production does not halt completely once SARS-CoV-2 viral loads go below the detection limit, which is typical following many viral infections.…”
Section: Discussionmentioning
confidence: 96%
“…While neutralizing antibodies are detected 1–2 weeks after symptom onset, it is less certain whether these antibodies are relevant for clearance of the virus or whether they only protect viral re-exposure. A better understanding of viral antibody interactions is critical to specify the optimal timing for neutralizing antibody treatments which may be more effective according to the stage of infection [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Indeed, recent trials of neutralizing antibody infusions demonstrate antiviral and clinical efficacy though only if dosed early in infection prior to clinical decompensation [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We began by evaluating the presence of RBD-specific IgG, IgM, and IgA antibodies by using a previously published enzyme-linked immunosorbent assay (ELISA) against the SARS-CoV-2 RBD antigen (16). In agreement with recent reports showing the waning of antibody levels in longitudinal convalescent plasma over time (14)(15)(16)(17), we observed that total RBD-specific immunoglobulin (Ig) levels, comprising of IgG, IgM, and IgA, gradually decreased between 6 and 31 weeks after the onset of symptoms ( Figure 1A). However, the percentage of convalescent individuals presenting detectable RBD-specific Ig levels remained stable, with a consistent seropositivity rate above 90% throughout the sampling time frame.…”
Section: Sars-cov-2 Rbd-specific and Spike-specific Antibody Levels Imentioning
confidence: 87%
“…This difference may be due to the fact that infected individuals may not have comparable antigen loads and uniform antibody responses over the time of the disease, as suggested by a study conducted on asymptomatic and symptomatic cases [6]. Interestingly, the kinetics of the humoral response was recently described in symptomatic (non-severe) and convalescent COVID-19 individuals and revealed that antibody levels against the receptor binding domain (RBD) of SARS-CoV-2 decline over time [7][8][9][10]. Despite these findings, long-term antibody responses remain to be fully characterized, particularly in hospitalized patients, and for instance, for those transferred to ICU and with very poor prognosis.…”
Section: Introductionmentioning
confidence: 99%